School Retention and Educational Quality. From dilemma to problem (Praxis Educativa, 2012)
The extension of compulsory schooling became, in many cases, a dilemma due to the presence in this equation of two terms considered antithetical: school retention and educational quality. Stereotypes and prejudice keep these terms divorced and pre-determine certain actions. Many efforts tend to preserve, to merely keep within the system without any change that would offer the possibility of a real inclusion. This practice leads towards, what is known as, a culture of mortification (Ulloa.1995), which includes both, those responsible to retain and those supposed to be retained. Four centuries ago, Comenio based the need to create a school for all on the personal and the social aspects, a school in which youth education would be in the hands of .youth educators. His wish, today a regulation in force, has not turned, yet, into an effective reality. The problem of school rejection is still present since the mere fact of attending classes does, by no means, guarantee inclusion, only achieved via a meaningful construction of knowledge. Our research shows that teachers educated in the school narrative of modernity, where the concepts of Duty and Sacrifice prevailed, become ineffective in a post-modern context. And in the misunderstanding that arises from the collision of narratives, suffering emerges and exclusion increases. To think about this problem implies to defy the certainties that are at the core of teacher education and training and to dare to question the way in which work is organized at school. This situation brings to the fore the challenge to reflect upon dominant teaching practices in order to turn compulsory education into true education. True education in the hands of true educators is, thus, advocated.
Keywords: retention; quality; exclusion; teacher education and training